A Criminological Review of Illegal Collection Practices by Illegal Parking Perpetrators in the Perspective of Differential Association Theory - Jovita Lituhayu Maheswari (Universitas Negeri Semarang, 2025)
This study examines the illegal levy practices carried out by illegal parking attendants from a criminological perspective through the Differential Association Theory. The research aims to analyze how illegal levy behavior is formed, studied, and maintained through social interaction between actors in public spaces. The method used is an empirical juridical approach with a descriptive-analytical nature that combines legal analysis with social realities in the field. Data was obtained through observation, interviews, and literature studies, then analyzed qualitatively. The results of the study show that the practice of illegal levies by illegal parking perpetrators is not just a spontaneous individual action, but is a pattern of deviant behavior learned in a certain social environment. This practice persists because of social tolerance, weak supervision and law enforcement, and the existence of informal power relations between perpetrators and the community. In practice, illegal levies are often accompanied by psychological pressure and non-verbal intimidation that encourages public compliance and normalizes illegal practices in daily life. From a criminological perspective, these behaviors are reproduced through repeated social interactions, collective justification, and learning techniques in the group of actors. This study concludes that illegal illegal parking levies are not only a violation of the law, but also a social phenomenon formed through the learning process, so its countermeasures require an integrated legal and criminological approach.